FOCAL GROUP: DATA COLLECTION INSTRUMENT IN RESEARCH IN EDUCATION - Santana, Iolanda Mendonça de; Silva, Maria de Fátima Gomes da (Cadernos de Educação Tecnologia e Sociedade, 2017)
The study presented here presents results of a research carried out in the Master of Education of the University of Pernambuco, whose main objective was to identify ways of experiencing interdisciplinarity in the pedagogical practices of the initial years of Elementary Education. The present clipping evidences the Focus Group (GF) as a technique for data collection in education research. The study was anchored in Crusoe's ideas (2014); Flick (2002); Gatti (2005); Kitzinger (2000); Lenoir (2008); Moreira (2002); Morgan (1997); Pombo (2005) Silva (2009); Thiollet (2011); Veiga & Gondim, (2001), among others. This research was guided by the qualitative approach of research and used as the main instrument for data collection the technique of focal group that for its execution counted on the participation of the moderator, observer, four teachers of the initial years of Elementary Education, two Supervisors of education and a technique of the Municipal Secretary of Education of the city of Nazaré da Mata, Zona da Mata Norte in the state of Pernambuco-Brazil. Data were analyzed using the content analysis technique, Bardin (2011), in an analytic-descriptive perspective. Reflexivity and partnership were categories of analysis, which are the main categories of interdisciplinary thinking. (Silva, 2009). The results of this research allowed us to conclude that the Focus Group technique in this study provided moments of deep reflection about interdisciplinarity and allowed the investigated teachers to understand that the forms with which they experience interdisciplinarity are at the first level of the relationship between the Knowledge, and multidisciplinary, this construction being linked to intersubjective and formative aspects, although the presence of two epistemic categories of interdisciplinary thinking, reflexivity and partnership were identified in the course of the discussions of the sessions with the group. It is also concluded that it is necessary to change the attitude of these teachers, which should be stimulated through the continuous training that should be linked to the elaboration of training policies by the Municipal Education Secretariat that allow a critical reflection on the pedagogical "what to do" In the direction of a permanent self-criticism that favors a teacher-making also based on the social dimension of interdisciplinarity.